Maternal and neonatal morbidity during off peak hours in a busy obstetric unit. Are deliveries after midnight more complicated?. (19th December 2013) - Hehir, Mark P.; Walsh, Jennifer M.; Higgins, Shane; Mahony, Rhona
Abstract Objective We sought to compare maternal and neonatal outcomes in deliveries occurring overnight with those in daylight hours. Design Prospective observational study. Setting Large national tertiary referral center. Population All singleton laboring nulliparous parturients delivering infants >500 g over a 2‐year period, 1 January 2008 to 31 December 2009. Methods Details of intrapartum characteristics and neonatal outcomes of deliveries occurring between midnight and 08.00 h were compared with deliveries occurring outside of these hours. Main outcome measures Maternal and neonatal morbidity. Results During the study period there were 8450 nulliparous deliveries. 2668 (31.6%) delivered between midnight and 08.00 h, and 5782 (68.4%) outside of these hours. There was a significant difference between the time periods in the number of babies born with a cord pH <7.1: 10.8% (44/406) of babies were born between midnight and 08.00 h, and 6.3% (63/1007) of babies were born outside these hours (p = 0.003). There was no significant difference in terms of Apgar score <7 at 5 min (p = 0.17). There was a trend toward a larger number of anal sphincter injuries occurring between midnight and 08.00 h (3% vs. 2.3%; p = 0.05). Conclusion Our findings suggest that infants are more likely to be born with a pH <7.1 and there was a trend toward an increased rate of anal sphincter injury during time periods when staffing levels are low and clinician fatigue may play a role in decision‐making and patient management. This may play a role in service provision planning and staff recruitment.